The importance of financial controls for maximizing results for small rural entrepreneurs - Vieira Filho, Warlei Alves; Furtado, Gislaine Mendes (Brazilian Journal of Science, 2024)
Brazil's agricultural sector is crucial for the economy and global food security, encompassing about 41% of the country's total land area and housing over 5 million agricultural establishments. According to the Brazilian Confederation of Agriculture and Livestock (CNA), agribusiness contributed 23.8% to the Gross Domestic Product (GDP) in 2023, highlighting its diverse production of agricultural commodities. While technological advancements have boosted productivity, a significant gap exists between large and small producers. Large producers often benefit from technological progress, whereas small producers—a significant portion of family farming—face substantial challenges. Family farming accounts for 67% of agricultural activity and 80% of global food production, yet it struggles with financial management, lack of knowledge, and limited access to credit and technology. Efficient rural management is essential for optimizing resources, reducing costs, and enhancing productivity on small farms. Implementing financial management practices, such as budgeting, cost analysis, and cash flow control, can help small producers make better use of their resources and lower expenses. Public policies like the National Program for the Strengthening of Family Farming (PRONAF) and the Food Acquisition Program (PAA) aim to support these producers by providing financing and securing markets for their products. Family farming holds significant potential for sustainable practices. With the right support, it can continue to play a vital role in the Brazilian economy and global food security, fostering a sustainable and prosperous future for the agricultural sector.